Current status of thoracic canal surgery in portal hypertension - Mañana Cattani, Julio (Cirugía del Uruguay, 2021)
In ascitic cirrhotic patients, the surgery of the thoracic duct follows precise indications. The pathological basis and surgical tactics based on twenty observations, are analyzed.